Measuring social norms of intimate partner violence to exert control over wife agency, sexuality, and reproductive autonomy: an item response modelling of the IPV-ASRA scale - Sabrina C. Boyce; Alexandra M. Minnis; Julianna Deardorff; Sandra I. McCoy; Sneha Challa; Nicole Johns; Sani Aliou; Mohamad Brooks; Abdoul-Moumouni Nouhou; Perman Gochyyev; Mark Wilson; Holly Baker; et al. (Reproductive Health, 2023)
Abstract Background The field of violence prevention research is unequivocal that interventions must target contextual factors, like social norms, to reduce gender-based violence. Limited research, however, on the social norms contributing to intimate partner violence or reproductive coercion exists. One of the driving factors is lack of measurement tools to accurately assess social norms. Methods Using an item response modelling approach, this study psychometrically assesses the reliability and validity of a social norms measure of the acceptability of intimate partner violence to exert control over wife agency, sexuality, and reproductive autonomy with data from a population-based sample of married adolescent girls (ages 13–18) and their husbands in rural Niger (n = 559 husband-wife dyads) collected in 2019. Results A two-dimensional Partial Credit Model for polytomous items was fit, showing evidence of reliability and validity. Higher scores on the “challenging husband authority” dimension were statistically associated with husband perpetration of intimate partner violence. Conclusions This brief scale is a short (5 items), practical measure with strong reliability and validity evidence. This scale can help identify populations with high-need for social norms-focused IPV prevention and to help measure the impact of such efforts.